Animal Science museum as a space for popularization and scientific discoveries (Research, Society and Development, 2020)
Science museums constitute a predominant cultural space visited by children and adolescents, and are most often used to consolidate knowledge acquired in formal education, as well as knowledge of empirical origin. The collection of the UNIPAR science museum has wild animals of the taxidermized Brazilian fauna, which, in turn, highlighting the fauna of the northwestern region of Paraná, fulfilling the role of museum collections, because besides being a collection, the pieces found in them should be conserved and researched, contributing to the knowledge and improvement of the scientific study in basic education, popularizing the knowledge. Within the dynamics of the museum it is still possible to develop scientific research that may result in discoveries such as an accessory spleen found in a species of Felidae, the description of such a structure is very scarce in the literature. Thus science museums collaborate directly with teaching, research and university extension.